First report of Rhodococcus spp. isolates causing stunting and lateral stem proliferation of Iresine herbstii ‘Aureo-Reticulata’ in Tunisia - Dhaouadi, Sabrine; Hamdane, Amira Mougou; Bahri, Bochra A.; Rhouma, Ali; Fichtner, Elizabeth J. (Phytopathologia Mediterranea, 2019)
AAVV